Molecular landscape and treatment paradigms of hepatocellular and cholangiocarcinoma: a multinational review = Molekulare Landschaft und Therapieparadigmen bei hepatozellulärem Karzinom und Cholangiokarzinom : eine multinationale Übersichtsarbeit - Skok, Kristijan; Stift, Judith; Schirmacher, Peter; Kashofer, Karl; Stauber, Rudolf; Ranković, Branislava; Lackner, Karoline (Zeitschrift für Gastroenterologie, 2025)
Hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) represent the most prevalent primary liver cancers and pose significant challenges in oncology. While their etiology and incidence vary globally, the molecular landscape of these tumors is increasingly understood, offering new opportunities for precision medicine. In this joint multinational review, we present a comprehensive analysis of the key molecular pathways involved in the pathogenesis of HCC and CCA, highlighting actionable targets for emerging therapies. Recent advances in molecular diagnostics have significantly influenced treatment paradigms for both cancers. In HCC, while genetic alterations have not yet led to established diagnostic or therapeutic applications, targeting vascular endothelial growth factor (VEGF), immune checkpoints, and tyrosine kinase pathways has demonstrated considerable therapeutic potential. In CCA, genetic profiling has uncovered actionable alterations, such as FGFR2 fusions and IDH1 mutations, driving the development of targeted therapies. The growing complexity of precision oncology underscores the need for standardized molecular testing and streamlined diagnostic workflows to ensure timely and effective treatment. This review also emphasizes the importance of collaborative efforts between clinicians, pathologists, and oncologists to optimize outcomes. By synthesizing the latest molecular insights and treatment trends, this review provides a valuable resource to guide the personalized management of HCC and CCA